Power Saving Strategies-Green Computing - Shobana, G; Avinash Wilson, J; Arun, P (International Journal of Computer Sciences and Engineering, 2025)
Green computing is one of the important aspects in which manufacturing, clearing and recycling of electronic devices are taken into account. The ultimate aim of green computing is to produce possibly less harm to the environment and to promote optimal usage of power in an eco-friendly manner. Equipping electronic devices in a large scale all over the globe leads to the environmental degradation because numerous tons of carbon-di-oxide is produced indirectly due to computation. A unique team is working in testing and applying eco-friendly materials in computation. The main idea is to reduce the environmental impact of industrial process along with innovative technological growth. In this paper we discuss about the average power wastage due to computing and also the ways of green computing effectively with power saving ideologies including natural resources and sensors.